2017
DOI: 10.1007/978-3-319-61322-2_14
|View full text |Cite
|
Sign up to set email alerts
|

Designing for Sustainable Urban Mobility Behaviour: A Systematic Review of the Literature

Abstract: Urban mobility poses one of the pressing challenges in cities undergoing growing urbanisation. In order to cope with this issue, a shift in behaviour is necessary towards more sustainable means of transportation. Technology can mediate the process of behaviour change, and concepts such as persuasive technology and reflective learning are approaches in this context. In order to investigate currently envisioned or implemented technological solutions, particular in the context of the smart city notion, this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In the literature, several reviews can be found on sustainable mobility or some of its single topics; limiting to some of the most recent ones only, here we refer to [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In [4], the effects of technology on promoting the shift in behavior towards sustainable transportation modes are investigated. Gonzales Aregall et al [5] reviewed green port strategies for reducing negative externalities on hinterlands.…”
Section: Related Workmentioning
confidence: 99%
“…In the literature, several reviews can be found on sustainable mobility or some of its single topics; limiting to some of the most recent ones only, here we refer to [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In [4], the effects of technology on promoting the shift in behavior towards sustainable transportation modes are investigated. Gonzales Aregall et al [5] reviewed green port strategies for reducing negative externalities on hinterlands.…”
Section: Related Workmentioning
confidence: 99%
“…In a previous work, we surveyed technological applications for behaviour change in the city [16]. A systematic literature review was conducted, exploring previously envisioned or implemented solutions, addressing urban mobility behaviour change.…”
Section: Related Workmentioning
confidence: 99%
“…Participatory design approaches facilitate democratization of design, empower people, and not least, emphasize diversity in the groups they include [26]. However, user involvement in the development of behaviour change applications is scarce in the smart city domain [16,28], as well as in other research fields concerned with sustainability themes [4]. Only a small percentage of works report the adoption of participatory design methods, or other forms of user engagement, during the design phase of the applications.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations